2004
DOI: 10.1016/j.orthres.2003.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic‐preconditioning does not prevent neuromuscular dysfunction after ischemia–reperfusion injury

Abstract: The primary purpose of this study was to evaluate ischemic‐preconditioning (IPC) as a means of improving tolerance to ischemia–reperfusion (IR) stress on neuromuscular function. A secondary objective was to isolate the area of injury within the neuromuscular unit responsible for contractile dysfunction after IR injury. Twenty‐eight male rabbits were randomly assigned to four groups (sham, IPC only, sustained ischemia only, IPC and sustained ischemia). The IPC protocol consisted of three cycles of 10 min of tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Others have reported a decrease in specific force following acute IRI [31,43]. In our study, the 70% loss in absolute muscle force in Veh controls resulted from the 20% loss in muscle mass and 60% loss in muscle-specific force; thus the observed deficits in force production are primarily attributable to the loss of specific force.…”
Section: Discussionsupporting
confidence: 53%
“…Others have reported a decrease in specific force following acute IRI [31,43]. In our study, the 70% loss in absolute muscle force in Veh controls resulted from the 20% loss in muscle mass and 60% loss in muscle-specific force; thus the observed deficits in force production are primarily attributable to the loss of specific force.…”
Section: Discussionsupporting
confidence: 53%
“…3a), providing the first evidence of motor nerve. Ischemic-preconditioning has previously shown not effective in preventing neuromuscular dysfunction induced by IR [9,51]. Conversely, force production induced by direct muscle stimulation was reduced similarly in saline-, MitoNAP- and MitoSNO-treated hindlimb muscles compared to the sham control (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…We performed a 28-day longitudinal study, in which we measured the maximal tetanic force production of the planter flexors in vivo via nerve stimulation or direct muscle stimulation. These protocols provide insight into neuromuscular transmission and force generating capacity of the muscle, respectively [9,42]. In un-injured mice (sham), force production resulting from nerve and muscle stimulations was indistinguishable (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in rat hind limbs subjected to 2 h of tourniquet ischemia and then examined 1–28 days later, electron microscopic analysis detected no changes in axons, Schwann cells or muscle fibers, but did detect multiple signs of degeneration in motor nerve terminals, including disruption of the presynaptic membrane, the appearance of vacuoles, and degeneration of mitochondria (Makitie and Teravainen, 1977; Tombol et al, 2002). Functional measurements also indicate that the neuromuscular junction is a major site of I/R injury (Eastlack et al, 2004). Baxter et al (2008) found that mouse motor nerve terminals are also selectively vulnerable to hypoxia/reoxygenation, an in vitro model of I/R stress.…”
Section: Introductionmentioning
confidence: 99%